Baudelaire et l’énigme de « J. G. F. » - Brix, Michel (Verbum – Analecta Neolatina, 2007)
The dedication "À J. G. F." appears twice in Baudelaire’s work. As a heading to Paradis artificiels (1860) the first time; and a second time in the 1861 edition of Les Fleurs du Mal, where the poem entitled "L’Héautontimorouménos" is addressed to this mysterious person. Up until now, these initials have guarded their secret. To whom do they belong? To this day, no mention has ever been made by critics that those initials match the forenames of a famous contemporary of the author, a doctor twice mentioned by Baudelaire, the alienist (psychiatrist) Jules Gabriel François Baillarger.